Pengaruh Teknik Effleurage Massage terhadap Nyeri Afterpains Post Partum di Bidan Sulastri di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Tahun 2022 - Susilawatik Susilawatik; Kartika Afrilina Tarigan; Kismiasih Adethia (PPNI UNIMMAN, 2023)
Afterpains are a common physiological complaint experienced by mothers during the postpartum period due to uterine contractions that occur after childbirth. This pain can disrupt comfort, inhibit the involution process, and affect the mother's physical and psychological well-being. Non-pharmacological treatment efforts such as the Effleurage Massage technique are an effective alternative because they can increase relaxation and stimulate the release of endorphins that play a role in reducing pain perception. This study aims to determine the effect of the Effleurage Massage technique on the level of afterpains in postpartum mothers at Midwife Sulastri, Percut Sei Tuan District, Deli Serdang Regency in 2022. The research design used was a quasi-experimental design with a one-group pretest-posttest without a control group. The study sample consisted of 45 postpartum mothers selected using the total sampling technique. Data were collected through observations with a numeric pain scale and analyzed using the Wilcoxon Signed Rank Test. The results showed that there was a significant decrease in pain levels after Effleurage Massage with a p value = 0.000 (<0.05). These findings demonstrate that the Effleurage Massage technique is effective in reducing the intensity of postpartum afterpains. Consequently, this massage can be used as a complementary therapy in postpartum midwifery care to increase comfort and accelerate the mother's recovery process.